Environmental noise pollution noise mapping, public health, and policy - Murphy, Enda; King, Eoin A. (Amsterdam Elsevier, 2014)
Environmental Noise Pollution: Noise Mapping, Public Health and Policy addresses the key debates surrounding environmental noise pollution with a particular focus on the European Union. Environmental noise pollution is an emerging public policy and environmental concern and is considered to be one of the most important environmental stressors affecting public health throughout the world. This book examines environmental noise pollution, its health implications, the role of strategic noise mapping for problem assessment, major sources of environmental noise pollution, noise mitigation approaches, and related procedural and policy implications. Drawing on the authors' considerable research expertise in the area, the book is the first coherent work on this major environmental stressor, a new benchmark reference across disciplinary, policy and national boundaries.--Provided by publisher.
Chapter 1: Environmental Noise Pollution -- Chapter 2: Principles of Environmental Noise -- Chapter 3: Environmental Noise and Health -- Chapter 4: Strategic Noise Mapping -- Chapter 5: Transportation Noise -- Chapter 6: Industrial and Construction Type Noise -- Chapter 7: Noise Mitigation Approaches -- Chapter 8: Conclusions and Future Directions -- Index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Noise pollution -- Environmental aspects; Noise pollution -- Health aspects; Electronic books